IT SYSTEMS ADOPTION AND ITS IMPACT ON THE FOOD AND AGRICULTURAL SECTOR - Woźniakowski, Tomasz; Jałowiecki, Piotr (Acta Scientiarum Polonorum. Oeconomia, 2013)
The paper contains an overview of Information and Communications Technology (ICT) implemented in food and agricultural enterprises. The description of the sector summarizes some unique features compared to numbers describing food production aspects in Europe. For better understanding of the whole phenomenon the paper describes an innovative processes and technology progress in general and in the sector as well. Important aspects and potential problematic areas such as factors that influence ICT deployment are shown and analyzed. Main focus is directed on the technologies of e-business and its impact on organizational aspect of the sector. Also the role of ICT in the innovation process and product has been reviewed and certain areas of improved activities compared and summarized. Very forward-looking technology in the agri-food sector is SOA. With a common data exchange standards, it is possible to transfer information between different units.